The Dilemma of Decentralization: “The Problem” of Development Discourse in India - S. Harikrishnan and Suraj Gogoi (KILA Journal of Local Governance, 2013)
While decentralization and “power to the people” seems to be vouched for and en- couraged at the national political arena, the implementation of decentralized gov- ernance has not come without bias. The paper discusses the success story of decentralized governance in Kerala, only to make a more stark comparison with the contradictory developmental path that the State is taking up with regard to the North-Eastern states of the country.